2022
DOI: 10.5539/jel.v11n2p63
|View full text |Cite
|
Sign up to set email alerts
|

Problems and Needs in Instructing Literacy and Fluency of Reading and Writing Skills of Thai L1 Young Learners

Abstract: The purposes of the current study were 1) to investigate problems in instructing literacy and fluency of reading and writing of Thai L1 young learners, and 2) to investigate needs in instructing literacy and fluency of reading and writing of Thai L1 young learners. There were 2 groups of participants including a group of 15 samples answering a questionnaire and a group of 10 samples taking part in an interview session. The instruments were 1) a questionnaire and 2) a structured interview to study problems in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
(18 reference statements)
0
9
0
1
Order By: Relevance
“…Based on the Table 2, 15 articles identified the use of the literacy movement as an effort to develop literacy skills in elementary schools. Specifically, 5 literacy movements can be used as an effort to build literacy skills in elementary schools, namely literacy culture strategies (Hyman et al, 2020;Imran et al, 2011;Liansari et al, 2021;Marmoah & Poerwanti, Suharno, 2022;Nuangchalerm & Intasena, 2022;Su & Ma, 2021), use of digital technology (Izhar et al, 2022;Mumpuni et al, 2021;Murti et al, 2020), procurement of reading books (Senen et al, 2021;Sri et al, 2021;Yasir et al, 2022), development of library facilities and character building (Farikah, 2019;Subur et al, 2022), take part in a national assessment (Hendrowati & Faelasofi, 2021). The number of research articles found in software Publish or Perish 8 with systematic objectives can be detailed in the Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the Table 2, 15 articles identified the use of the literacy movement as an effort to develop literacy skills in elementary schools. Specifically, 5 literacy movements can be used as an effort to build literacy skills in elementary schools, namely literacy culture strategies (Hyman et al, 2020;Imran et al, 2011;Liansari et al, 2021;Marmoah & Poerwanti, Suharno, 2022;Nuangchalerm & Intasena, 2022;Su & Ma, 2021), use of digital technology (Izhar et al, 2022;Mumpuni et al, 2021;Murti et al, 2020), procurement of reading books (Senen et al, 2021;Sri et al, 2021;Yasir et al, 2022), development of library facilities and character building (Farikah, 2019;Subur et al, 2022), take part in a national assessment (Hendrowati & Faelasofi, 2021). The number of research articles found in software Publish or Perish 8 with systematic objectives can be detailed in the Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The first finding, as many as 6 studies discussing literacy culture strategy planning conducted (Hyman et al, 2020;Imran et al, 2011;Liansari et al, 2021;Marmoah & Poerwanti, Suharno, 2022;Nuangchalerm & Intasena, 2022;Su & Ma, 2021). Planning a strategy for fostering literacy skills in elementary schools is a necessary part of creating a literate school environment, so it is essential to familiarize elementary school students with literacy activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These processes demand time and learners' concentration which might be an issue for young learners. In this case, BBL could be an alternative solution as it helps instructors design learning management that serves students' brain function, cognitive processes, and nature of learning (Intasena and Nuangchalerm, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise, the students are also expected to create written output that follows the lexical and grammatical rules of the language they use. This prepares students for the world of information they encounter after graduation (Intasena and Nuangchalerm, 2022).…”
Section: Introductionmentioning
confidence: 99%